Comparative analysis of cardiometabolic parameters in patients with coronary heart disease with and without non-alcoholic fatty liver disease - Dilnora B. Yusupalieva; Rano B. Alieva; Ulugbek I. Nizamov; Aleksandr B. Shek; Shoxista Axmedova; Nargiza Nurillaeva; Surayyo M. Shukurdjanova (Exploration of Cardiology)
Aim: Coronary heart disease (CHD) has been the leading cause of death worldwide for several decades. Non-alcoholic fatty liver disease (NAFLD), the most common liver pathology, is considered a risk factor (RF) for the development of CHD and a predictor of an unfavourable prognosis. Our study aimed to compare cardiometabolic parameters in patients with CHD with and without NAFLD. Methods: The study prospectively included 85 patients with CHD, 61 with NAFLD (group I) and 24 without NAFLD (group II). In both groups, a comparative analysis of RF, anthropometric parameters, lipidogram, glycemic profile, brachiocephalic arteries (BCA) ultrasound (USD), and heart structural and geometric parameters according to echocardiography (EchoCG) and coronary calcium (CC) parameters was performed. Results: Patients with CHD and NAFLD had statistically significantly higher levels of total cholesterol, very low-density lipoproteins, triglycerides, insulin, heart structural parameters, and CC. Conclusions: Thus, the relationship between NAFLD and CHD is two-way, and liver diseases can exacerbate the course of cardiovascular diseases (CVD).